The Shari’ah Foundation of Islamic Banking - Md. Thowhidul Islam (al-Afkar, Journal For Islamic Studies, 2025)
Islam prescribes a complete code of conduct for human life including economic activities. The prescribed Islamic code of conducts is generally refers to Shari’ah, on which Islamic banking has been founded. The most important characteristic of Islamic banking is to maintain its products and operations according to the principles of Shari’ah, which is based on the Holy Qur’an, Hadith, Ijma, Qiyas and Ijtihad. Islamic banking has rapidly been growing in the modern economic world as an alternative to the conventional banking. It is expected that Islamic banking operations will not only comply with the Shari’ah but also will contribute towards achieving the Maqasid-al-Shari’ah (objectives of Shari’ah), that is the ultimate welfare of the Muslim Ummah and the human being. The findings of several studies showed that Shari’ah compliance is the single most important factor for choosing Islamic banking. But unfortunately, many recent studies revealed that many Islamic banks are violating their obligation of Shari’ah compliance. Hence, the paper aims at understanding the Shari’ah foundation of Islamic banking with a view to examining that the modes of Islamic banking are based on the principles of Shari’ah. It also incorporates the major components of Shari’ah and its concept towards economic tools such as, ownership, wealth, money, capital, trust and accountability with the aim of having a comprehensive idea about the Shari’ah foundation of Islamic banking. The methodology used in this conceptual study is a critical analysis of literature survey. The literature on the concept of Shari’ah basis of Islamic banking are read to understand the basic components of Shari’ah and its principles to govern economic practices with a view to examining its application in Islamic banking industry and identifying the Shari’ah foundation of the modes and contracts used by the modern Islamic banking industry.